Coating Characterization of TiN & TiAlN on Burr Formation in Drilling – Pragmatic Investigation - Sivarao, Subramonian; Samsudin, Abdul Rahim; Taufik; Ammar, Abd Rahman (2007)
Burrs are source of dimensional errors, jamming and misalignment in the assembly process. They may cause short circuits in electrical components and may reduce the fatigue life of the part. Furthermore, burrs can be a safety hazard to personnel because they are usually sharp. This scientific research investigates the characterization of 8 mm diameter, 120o point angle of coated drill tool in burr formation. The exit burrs were investigated using two different types of popular coatings, namely TiN and TiAlN. The effect of cutting speed and feed rate of the tool in burr formation onto the workpiece are discussed. In this study, the exit burr height was measured using optical microscope. Moderately harder material, 304L series stainless steel was used in the evaluation of the super coatings. The experiments were conducted using CNC HAAS Milling Machine. These experiments can be classified as hard drilling based on the experimental values and machining conditions.